2014
DOI: 10.1093/icesjms/fsu060
|View full text |Cite
|
Sign up to set email alerts
|

Implications of stock recovery for a neighbouring management unit: experience from the Baltic cod

Abstract: Cod in the Baltic Sea is assessed and managed as two separate stocks, i.e. eastern and western Baltic cod. The eastern Baltic cod has recently started to recover after several decades of severe depletion. In the present study, we suggest that the recovery of the eastern Baltic cod population has also substantially increased cod abundance in a specific area of the adjacent western Baltic management unit. This is investigated through long time-series of spatially resolved stock assessment data supplemented by ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…Our data from archived otoliths collected in 2003 and 2004 indicate that mixing is not a recent phenomenon. This implies that eastern fish were also present in the area at times with much smaller population sizes of eastern Baltic cod than estimated for late 2000s to early 2010s (Eero et al, ), as also suggested by morphological data collected from otoliths (Hüssy, Hinrichsen et al, ). Our data further suggested the presence of a strong east–west gradient in mixing proportions in samples from 2003 to 2004, similarly to the pattern observed in contemporary data collected after 2011, although it should be noted that the samples represent much lower geographical resolution than the contemporary data set.…”
Section: Discussionmentioning
confidence: 55%
“…Our data from archived otoliths collected in 2003 and 2004 indicate that mixing is not a recent phenomenon. This implies that eastern fish were also present in the area at times with much smaller population sizes of eastern Baltic cod than estimated for late 2000s to early 2010s (Eero et al, ), as also suggested by morphological data collected from otoliths (Hüssy, Hinrichsen et al, ). Our data further suggested the presence of a strong east–west gradient in mixing proportions in samples from 2003 to 2004, similarly to the pattern observed in contemporary data collected after 2011, although it should be noted that the samples represent much lower geographical resolution than the contemporary data set.…”
Section: Discussionmentioning
confidence: 55%
“…(, ) for the 1990s and Eero et al. () for the spawning season 2012, also found no evidence of spawning activities of EBC in the Belt Sea.…”
Section: Discussionmentioning
confidence: 87%
“…(), Eero et al. () and Hüssy et al. () to the conclusion, that currently seasonal spawning migrations from the Bornholm Sea to the Arkona Sea take place.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations